KINETIC-PROPERTIES OF OSSEOUS PLATE ALKALINE-PHOSPHATASE FROM DIABETIC RATS - Rezende, A. A.; Petenusci, S. O.; Urbinati, Elisabeth Criscuolo [UNESP]; Leone, F. A. (Elsevier B.V., 1993)
1. Increased levels of bone alkaline phosphatase activity were observed in diabetic rats. These animals exhibited impaired bone development without concomitant alterations of the sequence of cellular transformations.2. Alkaline phosphatase activity was delayed in diabetic rats but the kinetic parameters for the hydrolysis of p-Nitrophenylphosphate (PNPP) were virtually the same observed for controls (N = 1.2 and K0.5 = 43 muM).3. Alkaline phosphatase from diabetic rats had a better affinity (K0.5 = 38 muM) for magnesium ions than controls (K0.5 = 9 1 muM).4. Zinc ions affected alkaline phosphatase activity from control and diabetic rats in the same way (K0.5 = 10 muM).